Divergence theorem in the $L_2$ -version. Application to the Dirichlet problem - Bogdanskii, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We propose the $L_2$ -version of the divergence theorem. The Green and Poisson operators associated with the infinitedimensionalversion of the Dirichlet problem are investigated.